Ewolucja controllingu w Energetyce Kaliskiej SA - Rubik, Jolanta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The changes of the energy market in Poland and in Europe need necessity of continuous monitoring and improving of costs and management effects. That is way most of energy enterprises go towards complex forms of management (e.g. controlling), which offer chance of early warning of threats and opportunities, current management and control of activities. This paper shows a pioneer and pattern case of controlling and its evolution in energy enterprise in Energetyka Kaliska SA. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 366-374